Stereotactic body radiotherapy of lymph node metastases under MR-guidance: First clinical results and patient-reported outcomes - Weykamp, Fabian; Herder-Wagner, Charlotte; Regnery, Sebastian; Hoegen-Saßmannshausen, Philipp; Renkamp, Claudia Katharina; Liermann, Jakob; Rippke, Carolin; Körber, Stefan A.; König, Laila; Buchele, Carolin; Klüter, Sebastian; Debus, Jürgen; et al. (Strahlentherapie und Onkologie, 2022)
Objective Stereotactic body radiotherapy (SBRT) is a noninvasive treatment option for lymph node metastases (LNM). Magnetic resonance (MR)-guidance offers superior tissue contrast and enables treatment of targets in close vicinity to radiosensitive organs at risk (OAR). However, literature on MR-guided SBRT of LNM is scarce with no report on outcome parameters. Materials and methods We report a subgroup analysis of a prospective observational study comprising patients with LNM. Patients received MR-guided SBRT at our MRIdian Linac (ViewRay Inc., Mountain View, CA, USA) between January 2019 and February 2020. Local control (LC), progression-free survival (PFS) and overall survival (OS) analysis were performed using the Kaplan-Meier method with log rank test to test for signiﬁcance (p < 0.05). Our patient-reported outcome questionnaire was utilized to evaluate patients’ perspective. The CTCAE (Common Terminology Criteria for Adverse Events) v. 5.0 was used to describe toxicity. - Results Twenty-nine patients (72.4% with prostate cancer; 51.7% with no distant metastases) received MR-guided SBRT for in total 39 LNM. Median dose was 27 Gy in three fractions, prescribed to the 80% isodose. At 1-year, estimated LC, PFS and OS were 92.6, 67.4 and 100.0%. Compared to baseline, six patients (20.7%) developed new grade I toxicities (mainly fatigue). One grade II toxicity occurred (fatigue), with no adverse event grade ≥III. Overall treatment experience was rated particularly positive, while the technically required low room temperature still represents the greatest obstacle in the pursuit of the ideal patient acceptance. - Conclusion MR-guided SBRT of LNM was demonstrated to be a well-accepted treatment modality with excellent preliminary results. Future studies should evaluate the clinical superiority to conventional SBRT.